[Rezension von: Jenkins, Philip, 1952-, Kingdoms of this world : how empires have made and remade religions] - Grant, Paul (A journal of church and state, 2025)
From Daniel's Babylon to Gandhi's South Africa, empires around the world and down through the ages have been effective at moving people across great distan